Moyamoya Disease: A Rare Entity Report of One Case (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Moyamoya disease is a disease of the cerebral vessels at the base of the cranium and is most prevalent in Japan. It is relatively rare in other parts of the world. Though few cases have been reported from different Asian and some European countries, to the best of our knowledge, no case of Moyamoya disease has been reported in our country so far. Here we report a case of Moyamoya disease in a 9 years old girl diagnosed in the department of neurosurgery of Bangabandhu Sheikh Mujib Medical University. We believe this is the first detected case in our country   DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11365   J Bangladesh Coll Phys Surg 2012; 30: 41-43